Anatomical and Physiological Characteristics of Reclamation Plant on the Post-Mining Land in Riding Panjang, Bangka - Nurtjahya, Eddy; Juairiah, Lina (LIPI Press, 2012)
Tin mining leaves disturbed land with sandy texture, damages natural drainage and habitats, and very low water holding capacity. The enrichment of species selection criteria for revegetating tin tailing with anatomical and physiological characters is needed to facilitate decision maker to select local species suitable for revegetation and to meet the economical need of the local people in post tin mining era. Besides exotic species, a handful of local tree species was planted recently. The need of more local species is especially needed to support biodiversity in mined land. Study of some leaf anatomical and root physiological characters of twelve months seedlings of leban(Vitex pinnata L-Verbenaceae) and ubak (Syzygium grande (Wight) Walp.Myrtaceae) planted in unmined land and tin-mined land in Bangka Island was conducted using wholemount and paraffi n methods. The fi ndings showedthat anatomical and physiological parameters of V. pinnata are more signifi cant than those of S. grande. Therefore, V. pinnata is more adaptive grown on tin tailing than S. grande.